Considerations of Solving Domestic Crises Derived from the Current Geo-Political Context - Marinescu, Liviu Mihail; Sirbu, Gabriela Elena (Acta Universitatis Danubius. Relationes Internationales, 2024)
Mankind has recently witnessed significant developments in the field of confrontations. In the beginnings, the classical, symmetric form of belligerence was used, where armed structures benefiting by a relatively similar potential would carry out the confrontation under the same conditions and circumstances. The next level, that of the asymmetric confrontation, is given by the existence of a geo-political actor using the superior armed forms versus another actor, with lower possibilities, which activates the guerrilla methods, subversive actions or fully clandestine actions in terms of applying the strikes. The most recent method, the hybrid confrontation is considered to be the newest and with the highest effect. This method entails the use of a mix of the two types of belligerence, at the same time with an extended information war. The crises from the perspective of the domestic security are mainly situated on the hybrid level, and the respective action pattern may be applied with maximum results in the current context.